The whispering skull - Stroud, Jonathan (Stroud, Jonathan. Lockwood & Co., 2015)
The agents of Lockwood & Co. are hired to oversee the exhumation of the deceased Edmund Bickerstaff, a Victorian doctor who reportedly tried to communicate with the dead while alive. Meanwhile, Lucy is distracted by urgent whispers coming from the skull in a ghost jar.